Pemahaman Bahasa Indonesia di Bidang Pariwisata Dalam Tour And Travel - Prizki Rispati Azhrini; Taufik Hidayat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Understanding the Indonesian language plays a crucial role in the tourism sector, especially in tour and travel. Indonesian not only serves as a communication tool but also as a means to convey information, promote culture, and build good relationships between tourism industry players and tourists. Effective communication using Indonesian allows for clear and accurate information delivery about tourist destinations, history, and local culture. This contributes to increased tourist satisfaction, as they gain a more informative and satisfying experience. Additionally, Indonesian helps promote local culture by explaining the meaning behind traditions and customs to tourists, thus enhancing their appreciation of Indonesia's cultural richness. The proper use of Indonesian in tour and travel services also has a positive impact on the local economy by attracting more tourists and increasing revenue from the tourism sector. Satisfied tourists tend to spend more time and money, which contributes to regional economic growth. Indonesian also plays an important role in building good relationships between tourists and local communities, creating a more authentic and meaningful experience for tourists.